Cruel harvest : US intervention in the Afghan drug trade - Mercille, Julien (Pluto, 2013)
Mainstream commentators claim that the Taliban are the culprits behind Afghanistan's rocketing drug trade and that the US military is waging war on drugs in Afghanistan to weaken the resurgency and keep the streets heroin-free. This book lifts the lid on the reality, showing that the US in fact shares a large part of the responsibility.